Cycles and instability in a Rock-Paper-Scissors population game: A continuous time experiment - Timothy N. Cason; Daniel Friedman; Ed Hopkins (University of California, Economics Department, 2012)
We report laboratory experiments that use new, visually oriented software to explore the dynamics of 3 x 3 games with intransitive best responses. Each moment, each player is matched against the entire population, here 8 human subjects. A heat map offers instantaneous feedback on current profit opportunities. In the continuous slow adjustment treatment, we see distinct cycles in the population mix. The cycle amplitude, frequency and direction are consistent with standard learning models. Cycles are more erratic and higher frequency in the instantaneous adjustment treatment. Control treatments (using simultaneous matching in discrete time) replicate previous results that exhibit weak or no cycles. Average play is approximated fairly well by Nash equilibrium, and an alternative point prediction, TASP (Time Average of the Shapley Polygon), captures some regularities that NE misses.
Keywords: C72; C73; C92; D83; 330; experiments; learning; mixed equilibrium; continuous time